1982
DOI: 10.1258/002367782780908724
|View full text |Cite
|
Sign up to set email alerts
|

Association of germfree mice with intestinal microfloras obtained from 'normal' mice

Abstract: A cultured microflora obtained from the caecum of a 'normal' mouse was given to 4 groups of germfree mice and was supplied 1x, 2x, 3x and 4x respectively at 5-day intervals. Another group received a 10-7 dilution of the caecal flora while a group associated with an 'SPF' flora served as control. The difference (measured by 8 parameters) between mice supplied with the cultured flora or with a 10-7 dilution, both given once only, was small. Supplying the flora 3x resulted in more 'normal' mice compared with mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

1983
1983
1997
1997

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 12 publications
1
26
0
2
Order By: Relevance
“…One group was moved to a so-called 'dirty cage' 6 weeks prior to induction of arthritis and another group was moved 3 weeks prior to induction. Comparable experiments in mice demonstrated that conventionalization takes place within 12 days [12,13].…”
Section: Ratsmentioning
confidence: 99%
“…One group was moved to a so-called 'dirty cage' 6 weeks prior to induction of arthritis and another group was moved 3 weeks prior to induction. Comparable experiments in mice demonstrated that conventionalization takes place within 12 days [12,13].…”
Section: Ratsmentioning
confidence: 99%
“…The villus: crypt ratio (VCR) of the ileum was determined as described earlier (Koopman et al, 1981). IgA-producing cells in the jejunum and ileum wall were measured as described earlier (Koopman et al, 1982a).…”
Section: Relative Caecal Weight (Rcw)mentioning
confidence: 99%
“…These were measured as described earlier (Koopman et al, 1981). The results are based on a pooled sample obtained from 8 mice.…”
Section: Volatile Fatty Acids (Vfa) and Non-volatile Fatty Acids (Na)mentioning
confidence: 99%
See 1 more Smart Citation
“…The caecum and parts of the ileum (± 5 cm) of both animals were homogenized in broth as described earlier (Koopman et al, 1983). From this homogenate a 10-2 dilution was made and 0'1 ml of this was spread on the surface of agar plates (Koopman et al, 1983).…”
Section: Preparation Of the Donor Microfloramentioning
confidence: 99%